Testing the theory of planned behavior in determining intention to use digital coupon among university students - Yakasai, Abu Bakar Mukhtar; Wan Jusoh, Wan Jamaliah (ELSEVIER, 2015)
Due to its ease of use and convenience, the use of internet and online purchases have become a trend among the younger generation. The increase in online shopping also affect the use of digital coupon. To date, there have not been many studies to investigate the influence of digital coupon use in Malaysia. It is the aim of this study to investigate the factors that influence the use of digital coupon among University students in Kuala Lumpur. A survey method was adopted in this study. A structured questionnaire was developed and used in the data collection. The questionnaires were distributed among students of an International University in Kuala Lumpur. A total of 392 respondents participated in this survey. The findings from the regression analysis showed that all the independent variables explained 50 percent of the variance in intention to use digital coupon. Attitude is the strongest predictor and followed by subjective norm and perceived behavioral control. All the relationships were tested significant at 99 percent significant level. Theoretically, this study lends support to the theory of planned behavior in explaining intention to use digital coupon. From the managerial perspectives, marketing managers should device necessary strategies and tactics to create adequate awareness and convey effective messages about the benefits of digital coupon to consumers so that positive attitude could be developed into actual usage of digital coupon. Thus, the resources used for this type of sales promotion will be converted into an actual increase in sales and profitability for the companies.